Formative assessment visual feedback in computer graded essays - Williams, Robert; Dreher, Heinz (Informing Science Institute, 2005)
In this paper we discuss a simple but comprehensive form of feedback to essay authors, based on a thesaurus and computer graphics, which enables the essay authors to see where essay content is inadequate in terms of the discussion of the essay topic. Concepts which are inadequately covered are displayed for the information of the author so that the essay can be improved. The feedback is automatically produced by the MarkIT Automated Essay Grading system, being developed by Curtin University researchers.